2019
DOI: 10.1007/s12220-019-00172-9
|View full text |Cite
|
Sign up to set email alerts
|

Some Remarks on the Pointwise Sparse Domination

Abstract: We obtain an improved version of the pointwise sparse domination principle established by the first author in [19]. This allows us to determine nearly minimal assumptions on a singular integral operator T for which it admits a sparse domination.where f p p,Q = 1 |Q| Q |f | p , and S is a sparse family of cubes of R n . Recall that the family of cubes S is called η-sparse, 0 < η ≤ 1, if for every cube Q ∈ S, there exists a measurable set E Q ⊂ Q such that |E Q | ≥ η|Q|, and the sets {E Q } Q∈S are pairwise disj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 19 publications
3
60
0
Order By: Relevance
“…This sparse domination principle was further generalized in the recent paper [58] by Lerner and Ombrosi, in which the authors showed that the weak L p 2 -boundedness of the more flexible operator…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This sparse domination principle was further generalized in the recent paper [58] by Lerner and Ombrosi, in which the authors showed that the weak L p 2 -boundedness of the more flexible operator…”
Section: Introductionmentioning
confidence: 94%
“…The main motivation to generalize the results in [58] comes from the application in the recent work [64] by Veraar and the author, in which Calderón-Zygmund theory is developed for stochastic singular integral operators. In particular, in [64,Theorem 6.4] Theorem 1.1 is applied with p 1 = p 2 = r = 2 to prove a stochastic version of the vector-valued A 2 -theorem for Calderón-Zygmund operators, which yields new results in the theory of maximal regularity for stochastic partial differential equations.…”
Section: Applicationsmentioning
confidence: 99%
“…This leads us to consider joint conditions involving Young functions that can be made strictly weaker than S 2+ε + T 2+ε for all ε > 0. Hence, we prove the commutator upper bound with these updated conditions with a version of the sparse domination principle introduced in Lerner and Ombrosi [10].…”
Section: Introductionmentioning
confidence: 92%
“…Next, our focus will be on Calderón-Zygmund operators satisfying the Dini condition. We begin with partially recalling, with only minor modifications, a sparse domination from Lerner [9] (also see Lerner, Ombrosi [10]). See also Ibánez-Firnkorn -Rivera-Ríos [7].…”
Section: Sufficient Conditionsmentioning
confidence: 99%
See 1 more Smart Citation